Cytosolic aspartate aminotransferase, a direct binding protein of kamikihito, regulates axon growth. Issue 1 (12th December 2015) - Watari, Hidetoshi; Shimada, Yutaka; Tohda, Chihiro
ABSTRACT: Aim: Alzheimer's disease (AD) is the most common cause of dementia. The aim of this study was to identify the direct binding proteins of kamikihito (KKT), a traditional Japanese Kampo medicine used as an anti‐AD drug. Method: Using the drug affinity responsive target stability (DARTS) method, cytosolic aspartate aminotransferase (cAST) was identified as the direct binding protein of KKT. Primary cultured cortical neurons were treated with amyloid beta (Aβ)(25–35), and cAST expression and activity were evaluated on western blotting and AST activity assay, respectively. To investigate the effects of AST inhibition and cAST knockdown on KKT activity, cortical neurons were treated with O ‐(carboxymethyl) hydroxylamine hemihydrochloride (OCHH; an AST inhibitor) or transfected with small interfering ribonucleic acid (siRNA) for cAST. The degree of axon atrophy was then evaluated under those conditions. Results: On DARTS analysis a 42 kDa protein underwent decreased proteolysis when KKT was present. Matrix‐assisted laser desorption/ionization time‐of‐flight tandem mass spectrometry (MALDI‐TOF‐MS/MS) indicated that the protein was cAST. cAST in Aβ(25–35)‐treated neurons had no change in expression level but the activity was reduced. In contrast, treatment with KKT restored cAST activity to control levels. Treatment of cortical neurons with Aβ(25–35) significantly decreased axonal density. KKT treatment restored axonal density, whereas the KKT‐induced increase in axonal density was diminished by OCHH treatment or knockdown of cAST. Conclusion: Aβ(25–35)‐triggered cAST inactivation may be related to axonal atrophy. KKT upregulates cAST activity, probably via direct binding to cAST, resulting in axonal growth.